2008
DOI: 10.4049/jimmunol.181.10.6955
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib Mesylate Inhibits CD4+CD25+ Regulatory T Cell Activity and Enhances Active Immunotherapy against BCR-ABL− Tumors

Abstract: I matinib mesylate (Gleevec) therapy remains the standard of care for patients with chronic myelogenous leukemia (CML).3 Designed as a selective competitive inhibitor of the Abelson (ABL) tyrosine kinases (BCR-ABL, v-ABL, c-ABL), this drug leads to growth arrest or apoptosis (1, 2). Imatinib also displays strong activity against the platelet-derived growth factor receptor, c-kit receptor, ABL-related gene, and their fusion proteins (1-3) and thus has also been used for the therapy of gastrointestinal stromal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 55 publications
5
105
0
3
Order By: Relevance
“…Therefore, the overall antitumor effects exerted by TKIs may arise concurrently, or even primarily, from the bystander targeting of immune cells (Figure 3). The relevance of tumor-cell-extrinsic targets for imatinib is supported by the observations that GISTs not mutated in Kit or Pdgfra can exhibit (Yang et al, 2008), MDSCs (Ko et al, 2009) and DCs (Borg et al, 2004), molecules in the T-cell receptor (TCR) proximal signaling mediate TKI response in Treg (Larmonier et al, 2008). TKI resistance, confined to the tumor microenvironment, can be induced in MDSCs by the GM-CSF-R pathway (Ko et al, 2010).…”
Section: Off-target Cancer Therapy With Tkismentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, the overall antitumor effects exerted by TKIs may arise concurrently, or even primarily, from the bystander targeting of immune cells (Figure 3). The relevance of tumor-cell-extrinsic targets for imatinib is supported by the observations that GISTs not mutated in Kit or Pdgfra can exhibit (Yang et al, 2008), MDSCs (Ko et al, 2009) and DCs (Borg et al, 2004), molecules in the T-cell receptor (TCR) proximal signaling mediate TKI response in Treg (Larmonier et al, 2008). TKI resistance, confined to the tumor microenvironment, can be induced in MDSCs by the GM-CSF-R pathway (Ko et al, 2010).…”
Section: Off-target Cancer Therapy With Tkismentioning
confidence: 76%
“…Blockade of T-cell activation becomes beneficial in cancer immunotherapy when the targeted cells are immunomodulatory cells that favor tumor progression, such as Treg. Imatinib has been reported to decrease Treg-suppressive function in vitro and in vivo, an effect mostly due to the inhibited phosphorylation of ZAP70 and LAT molecules following T-cell receptor stimulation Larmonier et al, 2008).…”
Section: Off-target Cancer Therapy With Tkismentioning
confidence: 99%
“…A number of reports have documented seemingly contradictory immunomodulatory effects of tyrosine kinase inhibitors, ranging from impaired T-cell responses [23][24][25] to enhanced responses to vaccination. 26 Although this study was not designed to look at differences in vaccine-induced immune responses between imatinib-and dasatinib-treated patients, our results suggest that patients with CML treated with tyrosine kinase inhibitors can mount effective immune responses to H1N1 vaccination. Seasonal influenza vaccine fails to produce cross-reactive antibodies to pandemic H1N1 27 because H1N1 virus and conventional influenza strains differ in their hemagglutinin and neuraminidase sequences, the two surface proteins that are the primary targets of neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 94%
“…However, in vitro studies showed that imatinib [31] and dasatinib impaired the proliferation and function of CD4 + CD25 + regulatory cells in a dose--dependent manner [32]. Further studies into the function of Tregs in patients treated with TKI are needed, especially given that encouraging data in a mouse model showed that imatinib enhanced active immunotherapy against BCR-ABL + tumors [33,34]. Finally, we analyzed the percentages of Th17 cells in peripheral blood of CML patients.…”
Section: Discussionmentioning
confidence: 99%